GENIALLY BASED LEARNING MEDIA USING POSNER'S CONCEPTUAL CHANGE THEORY TO ADDRESS MISCONCEPTIONS ABOUT HEAT - Nurvermadi, Rike; Maison, Maison; Falah, Hebat Shidow (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
This research aims to develop Genially based learning media and refers to Posner’s theory of conceptual change to address misconceptions about heat. This development research refers to the 4D model (Define, Design, Develop, Disseminate), with respondents of SMA Negeri 2 Tanjung Jabung Barat class XI IPA students who have studied heat material. The research instruments include a five-tier diagnostic test, materials, and media expert validation sheets. Based on validation by media and materials experts, the developed product achieved excellent results, with an average score of 91.96% for media experts and 90.18% for materials experts, respectively. The effectiveness test using the Wilcoxon Signed Ranks Test method showed a significant decrease in misconceptions, with a significance value of p = 0.010 (<0.005). The novelty of this research lies in the development of Genially-based learning media, combined with Posner’s Conceptual Change Theory, to reduce misconceptions specifically in heat-related material. The implication of this research shows that this media is not only effective in reducing misconceptions but also has the potential to be applied more widely in digital literacy-based physics learning, as well as a reference for developing similar media on other materials that are prone to misconceptions.